Reforming SOEs in Asia: Lessons from competition law and policy in India - Vijay Kumar Singh (Asian Development Bank Institute (ADBI), 2019)
India is one of the most significant countries of Asia, particularly in terms of its population and growing economy and markets. India has rapidly moved from a 'command and control' economy to free-market principles, and in this regard, one of the major reforms revamped the competition law. The new competition law introduced the principle of 'competitive neutrality' by bringing 'state-owned enterprises' (SOEs) under the purview of competition law regulation by virtue of defining 'enterprise' to include government departments engaged in economic activity. The Competition Commission of India (CCI) has penalized big SOEs like Coal India for violation of the Competition Act. However, looking from a reform perspective, generally there has been a bias toward state-owned enterprises by Governments in giving concessions, relaxing norms, and promoting finances. The biggest example is Air India - the national carrier. Other sectors would be railways, including container transport, state-owned banks, the health sector, and the energy sector. The objective of this paper is to examine the impact of competition law and policy on reforming SOEs in India. This will be done through looking at cases against SOEs in India and their impact on changing the behavior of SOEs vis-à-vis competition specifically and reforms generally.
Keywords: K210; K230; G3; G34; 330; state-owned enterprises; competition law and policy; competitive neutrality; public procurement